Renal Dysfunction and Recovery following Initial Treatment of Newly Diagnosed Multiple Myeloma - Benjamin A. Derman; Jochen Reiser; Sanjib Basu; Agne Paner (International Journal of Nephrology)
Introduction. Renal insufficiency (RI) in Multiple Myeloma (MM) portends a higher tumor burden and worse prognosis. Reversal of RI in newly diagnosed MM (NDMM) improves patient outcomes, but it is unknown if there is a disparity in renal recovery in NDMM between African Americans (AA) and non-African Americans. Methods. A retrospective chart review was conducted of 690 patients with NDMM at Rush University Medical Center from 2005 to 2016. 118 patients (59 AA and 59 non-AA) with NDMM and an estimated glomerular filtration rate (eGFR) < 90 mL/min/1.73 m2 at the time of diagnosis were identified and analyzed. The time to best renal response and best eGFR achieved during initial myeloma therapy were tabulated. Results. Median eGFR at the time of diagnosis was similar between the AA and non-AA groups (47.89 versus 51.95, p=0.56). Median absolute change in eGFR after initial therapy was significantly higher in the AA (+33.64) versus the non-AA group (+21.07, p=0.00183). This difference remained whether the baseline eGFR at diagnosis was <90 or <60 mL/min/1.73 m2. Discussion. AA patients with NDMM treated in the era of novel agents have greater improvement in renal function in comparison to non-AA patients, regardless of myeloma response. The biological underpinnings for this disparity require further investigation.